Soil Microbes Determine Outcomes of Pathogenic Interactions Between Radopholus similis and Fusarium oxysporum V5w2 in Tissue Culture Banana Rhizospheres Starved of Nitrogen, Phosphorus, and Potassium - Ochieno, Dennis M. W. (Frontiers in Sustainable Food Systems, 2022)
The contribution of soil biota on outcomes of pathogenic interactions between Radopholus similis and Fusarium oxysporum in nitrogen-starved tissue culture banana plants was investigated. The factorial screenhouse experiment (2 × 2 × 2) comprised of potted banana plants that had either been grown in sterile or non-sterile soil, and subjected to independent or combined inoculation with R. similis and F. oxysporum strain V5w2. Banana plants inoculated with R. similis were heavily colonized by the nematode with had high percentage dead roots and necrosis, while root biomass was low. Plants co-inoculated with R. similis and F. oxysporum had lower percentage dead roots and tended to have numerically lower nematode density compared to those treated with R. similis only, especially in non-sterile soil. Plants inoculated with R. similis had higher shoot dry weight, were taller with more leaves that were larger, compared to those not inoculated with the nematode. Plants grown in non-sterile soil had lower percentage dead roots, necrosis and R. similis density; they were also shorter with smaller leaves and lower biomass, compared to those from sterile soil. compared to those from sterile soil. Roots inoculated with R. similis had higher endophytic colonization by Fusarium spp., especially when co-inoculated with F. oxysporum V5w2 and grown in sterile soil. Darkened roots were associated with plants that were inoculated with R. similis and those that were grown in non-sterile soil. Results in the present study indicate that soil sterilization eliminates microbes that are suppressive to the R. similis-F. oxysporum disease complex. However, the pest-suppressive microbes also constrain the growth of banana plants under nitrogen-limited conditions. Whether R. similis should be considered a beneficial soil organism through banana plant growth promotion under N-deficient conditions remains debatable. In conclusion, pathogenic interactions between R. similis and F. oxysporum conditions are suppressed by a complex of soil microbes, which do not offer plant growth promoting services to tissue culture banana when starved of nitrogen.